The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1073/pnas.1719801115
|View full text |Cite
|
Sign up to set email alerts
|

MinE conformational switching confers robustness on self-organized Min protein patterns

Abstract: SignificanceMany fundamental cellular processes are spatially regulated by self-organized protein patterns, which are often based on nucleotide-binding proteins that switch their nucleotide state upon interaction with a second, activating protein. For reliable function, these protein patterns must be robust against parameter changes, although the basis for such robustness is generally elusive. Here we take a combined theoretical and experimental approach to the Escherichia coli Min system, a paradigmatic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 52 publications
5
118
0
1
Order By: Relevance
“…Diffusion in the cytosol is a simple means of protein transport that accounts for many self-organization processes [1]. To analyze how the interplay of diffusive protein transport and protein-protein interactions on a nanometer scale influences the protein patterns on the cellular scale, mass-conserving reaction-diffusion models have proven useful [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The study of reactiondiffusion systems in general goes back to Turing [19], who showed how patterns can emerge from a homogenous steady state when two reactive components have different diffusivities.…”
Section: A Background and Motivationmentioning
confidence: 99%
“…Diffusion in the cytosol is a simple means of protein transport that accounts for many self-organization processes [1]. To analyze how the interplay of diffusive protein transport and protein-protein interactions on a nanometer scale influences the protein patterns on the cellular scale, mass-conserving reaction-diffusion models have proven useful [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The study of reactiondiffusion systems in general goes back to Turing [19], who showed how patterns can emerge from a homogenous steady state when two reactive components have different diffusivities.…”
Section: A Background and Motivationmentioning
confidence: 99%
“…Here, on the basis of previous theoretical studies of intracellular protein dynamics [30, 32, 34, 79], we propose a minimal reaction-diffusion system to model Min localization in B. subtilis . Building on the idea of geometry sensing put forward in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…S1 and Tab. S2 ) and the values for the rate constants were estimated from previous work on protein pattern formation [30, 32, 34, 78]. The action on DivIVA and MinJ is accounted for effectively through space-dependent recruitment and detachment rates of MinD at membrane areas with a negative curvature; for details please refer to the Methods section ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MinD kann seinerseits auch bei MinE eine Konformationsänderung auslösen, welche diesem Protein eine stärkere Membranaffinität verleiht. Erst vor kurzem konnte Schwilles Arbeitsgruppe nachweisen, dass auch diese Wechselwirkung eine wichtige Rolle bei der Selbstorganisation und Musterbildung des Systems spielt .…”
Section: Wechselspiel Der Proteine Führt Zur Oszillierenden Reaktionunclassified